Greening of Polish Agriculture and Public Expenditure – Empirical Research Results - Jarczok-Guzy, Magdalena (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2025)
The aim of this article is to diagnose the factors determining the greening of agriculture in Poland and to assess the system of ecological payments for organic agriculture according to farmers’ opinions and the degree to which current forms of financing for the greening of agriculture are utilised. The research method adopted in the article was a questionnaire survey conducted among organic farmers from all voivodeships in Poland. The research procedure involved comparing the survey results and performing a statistical analysis of the responses using the χ2 independence test. As a result of the analysis, it was possible to assess the degree of subsidy utilisation by Polish farmers in stimulating ecological behaviour. The level of satisfaction of Polish farmers with support systems was also determined, and the greatest obstacles to the development of organic agricultural production were identified.